The Effect of Oral Clonidine at Different Doses on Post-Operative Analgesic and Hemodynamic Status in Upper Abdominal Surgery - Mondol, Mohammmad Shaddam Hoshain; Das, Rajat Shuvra; Ali, Md Arman; Shathi, Ishrat Jhahan; Miah, Mohammad Abdul Karim; Rahman, Chowdhury Md Mushfiqur; Azad, Khan Abul Kalam (Journal of Dhaka Medical College, 2021)
Background: Upper abdominal surgery (like- hepatobiliary surgery, gastrectomy, esophagectomy, hepatictomy, and whipples operations that involve large surgical incisions) lead to severe postoperative pain that lead to higher doses of opoids use in post-operative period as a result incidence of unwanted side effect and respiratory complication increase hospital stay and morbidity. To reduce the use of opioids clonidine can be used as a multimodal analgesic approach. It is reported that clonidine 150mcg intravenous (I/V) produce a similar analgesic effect to morphine 5mg in patient after orthopedic surgery. Because of its dose, route, and surgical variation it is very much important to specify the dose for upper abdominal surgery. Material and methods: After considering the inclusion and exclusion criteria the patients were randomized to receive Group: A (2mcg/kg oral clonidine) and Group: B (4mcg/kg oral clonidine), one hour (60minutes) before surgery as an oral premedication. All groups were compared for preoperative analgesic, sedation and anxiety level along with changes of heart rate and mean arterial pressure prior to premedication and post-operative periods as follows VAS (visual analogue score) pain scores. Result: The post-operative pain measured on VAS showed Group A expressed highest VAS at 6thpost-operative hour Group –B showed highest VAS at 14th post-operative hour. So it is very clear to us that pethedine requirement of Group B (4mcg/kg oral clonidine) is less than Group A (2mcg/kg oral clonidine). The oral premedication with clonidine at 2 microgram per kg or 4 microgram per kg for postoperative analgesia and hemodynamic stability of elective upper abdominal surgery patients. Conclusion: As a part of multimodal analgesic approach, 4mcg/kg oral clonidine premedication is effective to perioperative pain control and keep stable the haemodynamic in upper abdominal surgery J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 131-135